Bioactivity of essential oils of Cymbopogon citratus (DC) Stapf and Cymbopogon nardus (L.) W. Watson from Benin against Dinoderus porcellus Lesne (Coleoptera: Bostrichidae) infesting yam chips - Loko, Y.L.E.; Fagla, S.M.; Kassa, P.; Ahouansou, C.A.; Toffa, J.; Glinma, B.; Dougnon, V.; Koukoui, O.; Djogbenou, S.L.; Tamò, Manuele; Gbaguidi, F. (Springer, 2021)
Dinoderus porcellus L. (Coleoptera: Bostrichidae) is a most abundant and damageable pest of stored yam chips in West Africa. In view of the negative effects related to the use of synthetic chemical insecticide, it is important to develop alternative eco-friendly methods of control, such as the use of plant essential oils. The chemical composition and biological effects (repellent, antifeedant, contact and fumigant toxicity) of essential oils from Cymbopogon citratus (DC) Stapf and Cymbopogon nardus (L.) W. Watson were evaluated for the first time against D. porcellus. The chemical composition of C. citratus essential oil revealed that neral (24.64%), geranial (23.46%), and beta-pinene (21.90%) were the predominant compounds whereas citronellal (37.87%), nerol (19.88%) and citronellol (9.11%) were identified in C. nardus essential oil. Data showed that both essential oils were more effective as repellents and fumigant than the commercial insecticide Actellic 50 EC. The results also revealed the low contact toxicity of C. citratus and C. nardus essential oils against D. porcellus. However, similarly to Actellic 50 EC, C. citratus essential oil presented good antifeedant activity against D. porcellus and reduced yam chips weight loss. The results obtained suggest the good potential of C. citratus as both antifeedant and fumigant toxic agent against D. porcellus. While, C. nardus essential oil could be recommended as repellent. However, further studies are required to evaluate the insecticidal activity of both Cymbopogon essential oils under farmers’ storage conditions and to develop a good formulation as biopesticide.